A mixed Lagrangian-Eulerian study of Panguil Bay, Northwestern Mindanao, Philippines - Esguerra, Jonhneil P. (Miagao, Iloilo University of the Philippines Visayas, 2019)
A hydrographic study of Panguil Bay was concluded using a mixed Lagrangian-Eulerian methodology in an attempt to explain siltation, deposition, and transport of pollutants in the bay. The study specifically aimed at determining the surface circulation pattern of the bay and its dynamics in order to elucidate on the existing problems in the context of an integrated analysis of the hydrographic features of the bay. The independent variables were the tidal forces and wind stress. The dependent variables were water circulation and the supplementary variables such as surface temperature and salinity. This investigation employed indigenous methodology. Tidal heights were observed using tidal staffs installed near the mouth of five converging rivers. Surface wind was measured using a wind meter, windsock, and magnetic compass. The paths of water particles were tracked using surface and subsurface drifters equipped with GPS devices. The measurements were analyzed using time series plots, trajectories, spaghetti diagrams, vector plots, and cross correlation. The tidal data revealed that the ebb tide was stronger than the flood tide. The observed tidal height and phase deviated from NAMRIA predictions by about 0.29 m and 55 min. respectively. The characteristic of the surface circulation of Panguil Bay was found to be relatively weak with an average speed of 0.12 ms-1. The magnitude and direction of the winds were very variable during the sampling period due to the transition from the Northeast to southwest monsoon. Trajectories and spaghetti diagram revealed that the main water circulation was concentrated at the western portion of the bay, mainly as a clockwise ellipse along the Misamis Occidental coast. Tidal forcing was revealed as the more dominant influence to the circulation in the bay and was estimated at about five times more powerful than the wind forcing. The river systems and salinity were found as the third forcing of the circulation in the bay. Specifically, there were two salinity regimes observed in the area. Surface temperatures were uniformly high likely as a result of shallow depths relative to the deep open sea.
Thesis (M. S. Ocean Sciences) - Miagao, Iloilo : University of the Philippines Visayas, June 2019
Keywords: Panguil Bay -- Mindanao, Philippines